Exploring The Factors And Experiences Of Academic Procrastination Among Libyan Students: A Qualitative Study - Hetham M Alfaitori Alajaili; Yusawinur Barella (Departement of Mathematics Education, 2023)
Academic procrastination is a prevalent problem among students that has significant negative impacts on their academic performance and well-being. This qualitative study aims to explore the factors and experiences of academic procrastination from the perspective of students. The study involved in-depth interviews with a sample of students who have experienced academic procrastination. The data collected were analyzed using thematic analysis to identify common themes and patterns related to procrastination behavior. The results of this study provide insight into the underlying factors that contribute to academic procrastination and the experiences of students who struggle with this behavior. The study results indicate that there are several factors that influence students and contribute to academic procrastination, such as ineffective time management, lack of motivation or self disipline, lack of planning skills, fear of failure, and boredom with tasks.